Human Resource Management of Civil Servants and Islamic Education Quality: A Structural-Functional Analysis of Regional Education Governance - Amin, Ahmad Hidir; Erawati, Desi; Hilmy, Masdar (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Improvements in the quality of Islamic education are influenced not only by the competence of educators, but also by the effectiveness of public sector human resource management and the governance of education carried out by government bureaucracies. However, studies that specifically examine the role of State Civil Apparatus (ASN) human resource management in strengthening the governance of Islamic education at the regional level are still relatively limited. This study aims to analyze ASN human resource management strategies in improving the quality of Islamic education in East Kotawaringin Regency using a structural-functional theory perspective. This study uses a qualitative approach with a case study design. The research subjects included ASN in the regional education office, madrasah principals, and teachers at Islamic educational institutions. Data were collected through in-depth interviews, field observations, and documentation studies, then analyzed through the stages of data reduction, data presentation, and thematic conclusion drawing. The results of the study indicate that civil servant human resource management contributes to improving the quality of Islamic education through three main strategies, namely developing teachers' professional competencies, strengthening educational institutional governance, and coordinating policies between local governments and Islamic educational institutions. Teacher training programs, school management strengthening, and institutional support are important factors in improving the professionalism of educators and the quality of learning. This study contributes to the study of education governance by showing that public sector human resource management functions as a mechanism for strengthening the institutional capacity of Islamic education at the regional level.